Hyperspectral Imaging of Electrochemically Controlled Photoluminescence of Few Layer MoS2 in Widefield - ANUPAMA MUDIYANSELAGE (2025)
Molybdenum disulfide (MoS2) is one of the most important two-dimensional materials, exhibiting unique electrical and optical properties as it transitions from the bulk to the nanoscale. Typically, mechanical exfoliation and chemical vapor deposition (CVD) growth methods are used to prepare MoS2 nanosheets for optoelectronic studies and applications. However, mechanical exfoliation suffers from low yield and CVD based MoS2 growth involves high temperatures and complex costly set-ups. Hence, electro exfoliation has emerged as a promising scalable and cost-effective technique to produce few layer MoS2. In recent years, these MoS2 materials have gained significant importance in catalysis, as the efficient electron transfer facilitated by excitons and trions has proven particularly beneficial for reactions such as the hydrogen evolution reaction (HER). Also, according to the past research these few layers of MoS2 has considerable heterogeneity in their optical and electrical properties due to the presence of defects and discontinuities at the edges. Therefore, investigation of these spatial inhomogeneity is important to use these materials in the real-world applications.The present study was divided into two steps. Firstly, a simple electrochemical exfoliation method was employed to synthesise few-layer MoS2, avoiding the drawbacks associated with existing synthesis processes. The produced MoS2 was then characterised using Raman spectroscopy and photoluminescence spectroscopy to ensure the material's quality and structural integrity. Secondly, these produced few layer MoS2 was used to observe the change of the photoluminescence intensity across a single MoS2 flake and the asymmetric characteristics of trion photoluminescence with applied voltage using in-situ electrochemical setup. Hyperspectral imaging was employed, capturing spectral features from each pixel across a broad field of view rather than individual points.The result from the study indicates that the electro exfoliation method can produce MoS2 flakes with two or three layers on average, and the in-situ electrochemical characterisation showed significant spatial variations and a strong dependence on the voltage, highlighting the influence of electrical layer formation on the photoluminescence from excitons and trions. Therefore, the correlation between the PL intensity variations and applied voltages provides insights into the dynamics of excitons and trions under electrochemical conditions, paving the way for future studies to explore the full potential of 2D transition metal dichalcogenide materials in catalytic applications.